Strontium ranelate improves post-extraction socket healing in rats submitted to the administration of bisphosphonates - Gonçalves, Fernanda Castanheira [UNESP]; Mascaro, Bruno Arruda [UNESP]; Scardueli, Cássio Rocha [UNESP]; de Oliveira, Guilherme José Pimentel Lopes; Spolidorio, Luis Carlos [UNESP]; Marcantonio, Rosemary Adriana Chierici [UNESP] (Springer Nature, 2022)
The aim of this study was to evaluate the effect of strontium ranelate (Sr) on post-extraction socket healing in rats submitted to the administration of bisphosphonates. Sixty rats were submitted to the tooth extraction of the first lower molar after 60 days of the daily administration of saline solution (SS) or alendronate (ALN). Then, the animals were allocated into six groups namely CTR: administration of SS during the whole experiment, ALN: administration of ALN during the whole experiment, ALN/SS: application of SS for 30 days after extraction in animals previously treated with ALN, ALN/Sr: application of Sr for 30 days after extraction in animals previously treated with ALN, ALN/S60: ALN therapy interruption 30 days before the extraction followed by the application of SS for 60 days, and ALN/Sr60: ALN therapy interruption 30 days before the tooth extraction followed by the application of Sr for 60 days. The healing of the post-extraction sockets was evaluated by microCT and histomorphometry. The use of ALN induced partial bone necrosis, inflammatory infiltration, and a delay in soft tissue healing; the use of Sr improved the connective tissue organization. Sr has subtle positive effects on the post-extraction healing in animals submitted to the administration of bisphosphonate.
Keywords: Bisphosphonates; Bone healing; Pre-clinical study; Strontium ranelate; Tooth extraction